Electron relaxation and mobility in the inverted band quantum well CdTe/Hg₁₋xCdxTe/CdTe - Melezhik, Ye.O.; Gumenjuk-Sichevska, J.V.; Sizov, F.F. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
Electron relaxation processes at nitrogen temperatures in CdTe/Hg₁₋xCdxTe/CdTe quantum well (QW) with an inverted band structure is modelled. In this
structure, scattering by longitudinal optical phonons, charged impurities, acoustic phonons
and interfaces were taken into account. It was found that for undoped and lightly doped
QWs (concentration of background n-type charged impurities in the well is 10¹⁴ – 10¹⁶ cm-³
or less), for x close to the band inversion value 0.16, the electron mobility grows
considerably when the QW width decreases. This mobility is higher for samples with
smaller concentrations of charged impurities.